Continually Working : Black Women, Community Intellectualism, and Economic Justice in Postwar Milwaukee - Moten, Crystal, 1982- (Book collections on Project MUSE., 2023)
"Continually Working tells the stories of Black working women who resisted employment inequality in Milwaukee, Wisconsin from the 1940s to the 1970s"--